Lexical Specification of Prosodic Information in Swedish: Evidence from Mismatch Negativity - Zora, Hatice; Riad, Tomas; Schwarz, Iris-Corinna; Heldner, Mattias (Frontiers in Neuroscience, 2016)
Like many of the other Germanic languages, the Swedish stress system has mostly been given a phonological analysis. Recently, however, the central role of morphology has started to be recognized. Similar to the lexical specification of tonal accent, the Swedish stress system is claimed to be morphologically determined and morphemes are thus categorized as prosodically specified and prosodically unspecified. Prosodically specified morphemes bear stress information as part of their lexical representations and are classified as tonic (i.e., lexically stressed), pretonic and posttonic, whereas prosodically unspecified morphemes receive stress through a phonological rule, which is right-edge oriented, but sensitive to prosodic specification at that edge. The presence of prosodic specification is inferred from vowel quality and vowel quantity; if stress moves away, vowel quality and quantity change radically in phonologically stressed morphemes whereas traces of stress remain in lexically stressed morphemes. The present study is the first to investigate if stress is a lexical property of Swedish morphemes by comparing the mismatch negativity (MMN) responses to vowel quality and quantity changes in phonologically stressed and lexically stressed words. In a passive oddball paradigm, 15 native speakers of Swedish were presented with standards and deviants, which differed from the standards in formant frequency and duration. Given that vowel quality and quantity changes are associated with morphological derivations only in phonologically stressed words, the MMN responses are expected to be larger in phonologically stressed words than in lexically stressed words that lack such an association. The results indicated that the processing differences between phonologically and lexically stressed words were reflected in the amplitude and topography of the MMN responses. Confirming the expectation, the MMN amplitude was larger for the phonologically stressed word than for the lexically stressed word and showed a more widespread topographic distribution. The brain did not only detect vowel quality and quantity changes but also used them to activate memory traces associated with derivations. The present study therefore implies that morphology is directly involved in the Swedish stress system and that changes in phonological shape due to stress shift cue the upcoming stress and the potential addition of a morpheme.